The identification of novel missense variant in ChAT gene in a patient with gestational diabetes denotes plausible genetic association - Oluwole Oluwafemi G.; Arowolo Afolake; Musa Ezekiel; Levitt Naomi; Matjila Mushi (Open Medicine, 2025)
Gestational diabetes mellitus (GDM), the most common metabolic complication of pregnancy, is associated with a 50% increase in subsequent risk for type 2 diabetes. There is increasing interest in identifying biomarkers that may facilitate the stratification of subsequent type 2 diabetes risk among women with GDM. In this study, we considered the choline acetyltransferase (ChAT) gene. CHAT plays a critical role in acetylcholine synthesis and regulates insulin secretion from the pancreatic islet to maintain glucose homeostasis.